Study on adsorption and photodegradation of acid orange 51 in aqueous solution in the presence of various metal oxides - 273247 Khoo, Sook Kuen (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Kimia Industri) - Universiti Teknologi Malaysia, 2004